Implementing communication strategies in listening /speaking classes at the CFL-Can Tho University : - Đặng, Thị Kim Mai (Trường Đại học Cần Thơ, 2007)
Content of the book include: Introduction; theoretical framework of CSs; Research methodology; results; discussion, limitations and recommendations.